Assessing the role of urologists and general surgeons in the open repair of bladder injuries: Analysis of a large, statewide trauma database. Issue 6 (December 2019) - Leong, Joon Yau; Rshaidat, Hamza; Tham, Elwin; Mitsuhashi, Shuji; Chung, Paul H.
Abstract : BACKGROUND: Bladder injuries often occur in the setting of polytrauma, and if severe, may require open surgical repairs. We assess the role of urologists and general surgeons (GS) in the open surgical management of bladder injuries and their outcomes in a traumatic setting. METHODS: Patients who underwent open bladder injury repair secondary to trauma from 2000 to 2017 by urology or GS were identified in the Pennsylvania Trauma Outcome Study database by International Classification of Diseases—9th Rev.—Clinical Modification procedure codes (57.19–57.93). Patient demographics, initial trauma assessment, length of hospital stay, associated complications, and mortality were evaluated. Urology management of a bladder injury was defined by documentation of a urologist in the operating room or urological consultation during the hospital stay. GS management was defined by documented bladder repair without urology involvement as described previously. RESULTS: Of 624, 504 patients in the database, 701 met inclusion criteria (419 managed by urology, 282 by GS). The most commonly performed procedure was suturing of bladder lacerations (80.5%). On univariate analysis, GS was more likely to manage patients with penetrating injuries and those who required exploratory laparotomy less than 2 hours upon arrival. Urology was more likely to manage patients with concomitant pelvic fractures and higher Injury Severity Score (ISS). On multivariate analysis, higher ISS was predictive of urology management (odds ratio, 1.83; 95% confidence interval, 1.17–2.87, p = 0.008), while patients who required urgent exploratory laparotomy was predictive of GS management (odds ratio, 0.34; 95% confidence interval, 0.21–0.55, p < 0.001). Patients with concomitant pelvic fractures (n = 318) were also more likely to have higher ISS ( p < 0.001) and were more likely to be managed by urology (odds ratio, 1.52; 95% confidence interval, 1.01–2.30, p = 0.046). Mortality, length of hospital stay, and complication rates were not significantly different between the two specialties and among individual procedures. CONCLUSION: Our study describes the landscape of traumatic bladder repairs between urology and GS. GS may maintain similar patient outcomes when managing select cases of traumatic bladder injuries in the absence of urologists. LEVEL OF EVIDENCE: Therapeutic, level IV.